THE NATURE OF THE SUPERVISION OF THE COUNCIL OF REPRESENTATIVES ON THE FUNCTION OF LEGISLATION IN INDONESIA - santi indriyani; Febrian Febrian; Zen Zanibar (Faculty of Law, Universitas Pekalongan, 2023)
The House of Representatives is the holder of legislative power, which is expected to be able to produce quality legislative products in accordance with the legal needs of the community. However, the reality was the opposite of what was expected, resulting in public rejection. so that a judicial review must be submitted to the Constitutional Court. The purpose of this article is to find out how the nature of supervision of the council of people's representatives on the functions of law in Indonesia. The research method used is a normative legal research method with a qualitative approach to provide a descriptive explanation. The results of research analysis related to the nature of the DPR's oversight of the legislative function in Indonesia indicate that the supervisory function consists of the legislative function, democratic values, the value of balance, the value of truth, the value of benefits, and the principles contained in the DPR's supervisory function.